Electrochemical corrosion parameters for active and passive reinforcing steel in carbonated and sound concrete - Muazzam G. Sohail (14778871) (2023)
The electrochemical corrosion parameters, such as corrosion potential, corrosion current density, and the Tafel constants are necessary inputs for the corrosion modeling in reinforced concrete. Literature shows large variability in their values, whereas the data are scarce for the carbonated concrete. This paper presents a range of corrosion parameters for the active steel in carbonated and the passive steel in noncarbonated concrete. Forty-eight singly reinforced concrete cylinders were cast, of which 24 were carbonated and the others were sound samples. Potentiodynamic polarization curves were obtained at three different scan rates and extrapolated to extract the corrosion parameters. To validate these parameters, a macrocell corrosion system was simulated using FEM-based Comsol multiphysics® software. The numerical results were compared to two experimental studies. A natural dispersion in the values of corrosion parameters for both active and passive steels was observed. The average Stern–Geary constant was 54 and 47 mV for active and passive steels, respectively. Numerical simulations with the obtained parameters predicted the macrocell corrosion in partially carbonated concrete with a high accuracy. The presented values of corrosion parameters in this study could help researchers and engineers to simulate the corrosion phenomena in concrete accurately. Other Information Published in: Materials and Corrosion License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1002/maco.202112569